A mechanistic model for partial preferences - Berec, L; Krivan, V (Theoretical population biology, 2000)
Classic prey optimal foraging model assumes that individual predators are globally omniscient; that is, they have exact knowledge of prey population densities in the environment. This study examines a spatially explicit individual-based model of a one-predator two-prey system where individual predators are assumed to be omniscient only locally, i.e., to know prey population densities only in the range of their perception. Due to local variations in prey numbers, the probability of acceptance of less profitable prey shifts from the zero-one rule to a gradually decreasing function, for which an explicit formula is derived, giving way to partial preferences. A corresponding predator functional response to more profitable prey is shown to have a sigmoid-like form.
Keywords: Population Density; Behavior, Animal; Animals; výběrové chování; stravovací zvyklosti; Movement; Perception; percepce; Models, Psychological; predátorské chování; chování zvířat; zvířata; Predatory Behavior; Feeding Behavior; pohyb; hustota populace; Choice Behavior; psychologické modely